Noah's Art : Outdoor Animal Sculpture Exhibition. (New York : City of New York, 1989)
Bergmann, Meredith ; Chin, Mel ; Dow, Bruce ; Nebraska Gifford, J. ; Cramer, Timothy ; Gillen, Ann ; Gross, Chaim ; Kadishman, Menashe ; Lucchesi, Bruno ; Nelson, Judson ; Offner, Elliot ; Rodriguez, Jorge Luis ; Rupp, Christy ; Sasaki, Toshio ; Singer, Steven ; Slavin, Arlene ; Steir, Pat ; Watkins, Tim
Noah's Art : Outdoor Animal Sculpture Exhibition, Central Park, New York City, September 19 - December 3, 1989
boek